Introduzione (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
To present the first issue of BioLaw Journal – Rivista di BioDiritto, the members of the Scientific Committee have been invited to develop some considerations upon the relationship between Law and the Life Sciences. The themes proposed to the Italian members of the Committee respectively dealt with the main features of this relationship, with the most significant changes the relationship faced in the last decade, with the value of interdisciplinarity and with limits and potentialities of courts’ interventions in issue related to the life sciences. The members of the Committee coming from different countries, moreover, gave an insight of this relationship in their home jurisdictions. The global reading of these short contributions offers a profound and stimulating idea of the state of art of the relationship between law and life sciences and highlights the most challenging issues at stake.